Building a scalable microservice architecture with Envoy, Kubernetes, and Istio (O'Reilly, 2019)
"Microservices and containers have taken the software industry by storm. Transitioning from a monolith to microservices enables you to deploy your application more frequently, independently, and reliably. However, microservice architecture has its own challenges, and it has to deal with the same problems encountered while designing distributed systems. Enter service mesh technology to the rescue. A service mesh reduces the complexity associated with microservices and provides functionality like load balancing, service discovery, traffic management, circuit breaking, telemetry, fault injection, and more. Istio is one of the best implementations of a service mesh at this point, while Kubernetes provides a platform for running microservices and automating deployment of containerized applications. Join Samir Behara (EBSCO) to go beyond the buzz and understand microservices and service mesh technologies. This session was recorded at the 2019 O'Reilly Software Architecture Conference in San Jose."--Resource description page